The importance of C-H......N, C-H......π and π......π interactions in the crystal packing of the isomeric N1,N4- bis((pyridine-n-yl)methylene)-cyclohexane-1,4-diamines, n = 2, 3 and 4 - Lai, C.S. (2014)
10.1039/b613603f